ANXIETY IN D.H LAWRENCE'S "LADY CHATTERLEY'S LOVER": A PSYCHOANALYTIC APPROACH - RATMAWATI , SEFTY DWI (2007)
The major problem of this study is to eludicate how anxiety of lady Chatterley is reflected in D.H Lawrence Lady Chatterley Lovers. The objectives of the study are to analyze the novel based on their psychoanalytic approach. The writer uses a qualitative method whose data are based on primary source, the novel D.H Lawrence Lady Chatterley Lovers itself and secondary source, such as D.H Lawrence's biography and other data dealing with research. The data collection is documentation and technique of data collection is descriptive. Based on the analysis, the researcher draws some conclusion. Firstly, the novel D.H Lawrence Lady Chatterley Lovers is based on Lawrence's biography. Secondary, D.H Lawrence shows the conflict in the family that given impact on Lady Chatterley in her anxiety. Third, though his creation of his character and characterization, setting, plot and theme, the novel gives a clear description that anxiety experienced by Lady Chatterley.